Hemograma de fêmeas suínas durante a gestação, lactação e vazias, criadas no estado do Rio Grande do Sul - Fernandes, Roberta Ribeiro (2001)
Changes in the hemogram constituents of sows in different phases of the reproductive cycle, raised in the state of Rio Grande do Sul, were assessed. In order to do this, 129 blood samples of healthy Landrace, Large White and crossbreeding sows were used. The samples, according to the phase of the reproductive cycle, were stratified in four groups: pregnancy1 (from 0 to 80 days of pregnancy), pregnancy 2 (from 81 to 114 days of pregnancy), lactation and nonpregnancy. The average values and the standard deviation of the hemogram constituentes in the different groups were: pregnancy1: erythrocytes 6.10  0.88  106/mm3, globular volume (GV) 37.53  3.44 %, hemoglobin concentration (Hb) 12.73  1.22 g/dl, mean corpuscular volume (MCV) 61.99  6.26 fl, mean corpuscular (MCHC) 34.02  1.12 %, number of leukocytes (mm3) 12775  1965, band neutrophils 79  96, mature neutrophils 4345  1291, lymphocytes 7076  1480, monocytes 312  261, eosinophils 941  568 and basophils 23  64; pregnancy 2: erythrocytes 6.97  1.06  106/mm3, GV 35.74  3.7 %, Hb 12.44  1.45 g/dl, MCV 51.84  5.6 fl, MCHC 34.77  1.17 %, number of leukocytes (mm3) 14706  2107, band neutrophils 103  142, mature neutrophils 5768  1119, lymphocytes 7772  1354, monocytes 366  219, eosinophils 669  450 and basophils 27  79; sow in lactation: erythrocytes 5.74  0.63  106/mm3, GV 34.40  3.08 %, Hb 11.77  1.19 g/dl, MCV 60.03  7.10 fl, MCHC 34.20  1.43 %, number of leukocytes (mm3) 12504  2246, band neutrophils 53  101, mature neutrophils 5641  1491, lymphocytes 5687  1485, monocytes 393  265, eosinophils 697  342 and basophils 33  63; nonpregnant sows: erythrocytes 6.17  1.18  106/mm3, GV 34.89  3.24 %, Hb 11.47  1.33 g/dl, MCV 57.51  7.28 fl, MCHC 32.85  163 %, number of leukocytes (mm3) 1431  4058, band neutrophils 58  71, mature neutrophils 5928  1555, lymphocytes 7161  2823, monocytes 316  253, eosinophils 834  667 and basophils 13  49. It can be concluded that there is an individual variation of the hemogram constituents inside each considered group and also according to the reproductive phase. A decrease in the relation between lymphocytes and neutrophils and lactation advance was also verified as well as an increase in the absolute average values of lymphocytes and mature neutrophils as pregnancy evolves.